2004
DOI: 10.1002/chem.200400311
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Configuration in the Nucleophilic Substitution Reactions of Some Nine‐Membered Ansa Derivatives of Cyclotriphosphazatriene

Abstract: X-ray crystallographic evidence shows that nucleophilic substitution reactions of two different types of cyclophosphazene derivatives with relatively rigid nine-membered ansa rings leads to the first demonstration of retention of configuration in these molecular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…It has now been demonstrated crystallographically that inversion of configuration takes place in nucleophilic substitution reactions of macrocyclic phosphazene compounds containing a sixteen-membered ansa ring system, whereas retention of configuration occurs in cyclophosphazenes containing nine-membered ansa rings. [13] We are currently investigating analogous cis-ansa cyclophosphazene compounds with ring sizes intermediate between nine and sixteen to determine at which point or in which range of ring sizes retention changes to inversion. The work will be greatly facilitated by using a marker, such as the spiro-propanoxyamino group, which can be used to distinguish above and below the plane of the cyclophosphazene ring, and hence to investigate retention versus inversion mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has now been demonstrated crystallographically that inversion of configuration takes place in nucleophilic substitution reactions of macrocyclic phosphazene compounds containing a sixteen-membered ansa ring system, whereas retention of configuration occurs in cyclophosphazenes containing nine-membered ansa rings. [13] We are currently investigating analogous cis-ansa cyclophosphazene compounds with ring sizes intermediate between nine and sixteen to determine at which point or in which range of ring sizes retention changes to inversion. The work will be greatly facilitated by using a marker, such as the spiro-propanoxyamino group, which can be used to distinguish above and below the plane of the cyclophosphazene ring, and hence to investigate retention versus inversion mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Previous work has shown that the sixteenmembered ring of the cis-ansa macrocyclic cyclophosphazene derivative 1 is sufficiently large and flexible to take up both cis and trans configurations as a result of nucleophilic substitution reactions, [7,8] and so this same macrocyclic ring was incorporated into compound 3. Reaction of compound 3 with a range of mononucleophiles (2-naphthol, phenol, pyrrolidine and aniline) with different steric demands and different nucleophilicities gave examples of the monosubstituted compound 4 (4a, X = 2-naphthoxy; 4b, X = phenoxy) and of the disubstituted compounds 5a, 5b, 5c and 5d, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible meso form for Type II(4), Type II(5), Type II(7) Type II (8) and Type II (9) configurations. Hence all derivatives would be racemates which are shown for Type II(5) cis (55* [64], 56a [93], 56b [82]), Type II(5) trans (57 [76]), Type II(7) cis (58 [50]). …”
Section: Five Substituted (X Y a B C)mentioning
confidence: 98%
“…The case of the reaction of compound (9) with the silylated derivative of (2) provides another subtle change in the nature of the nucleophile, further complicated by this reaction being largely driven by the strengths of the Si-F being formed [17 and refs therein]. Much remains to be explained, such as the observation that the mono-ansa compound (4) reacts with pyrrolidine with retention of configuration [45].…”
Section: This Raises the Further Question To What Extent The Spiro Momentioning
confidence: 99%